Integrating the Value of Independence into a Digital Storybook for Fifth-Grade Students: A Design Study - Puspadi, Ketut Ayu Dewi; Artini, Luh Putu; Utami, I Gusti Ayu Lokita Purnamika (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
. Studies on the use of a digital storybook for teaching English to young learners have been abundant; however, the integration of independence values into the story for elementary school students in Indonesia has received limited attention. Independence is one of the characters that educate young learners to become responsible and self-reliant. This study aims to design a digital storybook that integrates independence value into English language learning materials for fifth-grade students. Using a qualitative Design-Based Research (DBR) approach, this study employed a design framework as the main research instrument, derived from character education theory, Teaching English to Young Learners (TEYL), and multimedia learning theory. Data were collected through the analyses of curriculum policies, English textbooks, children’s literature, character education, and multimedia learning. This study produced a digital storybook entitled Lisa Can Do It, which can be expected to become a medium to learn English and at the same time educate children about independence value. Findings indicate that character-based digital storybooks demonstrate the potential to integrate language learning with character education, providing a foundation for the design and implementation of digital learning materials integrated with character in English language education in elementary schools. Further research should focus on the implementation of the product to evaluate its impact on student learning outcomes.